The Effectiveness of Shuttle-Run and Zigzag Run Training on the Agility of Football Players - Alimuddin, Alimuddin; Yudiramawan, Yudiramawan; Komaini, Anton; Gemaini, Andri; Haris, Fahmil (Universitas Negeri Semarang, 2023)
This research was motivated by his weakness to actual agility, this was seen when he was unable to spill the ball while running fast and was unable to take another path without losing balance. The purpose of this study was to see how shuttle-run and zig-zag run training to improve the skills of PERSIMURA U-17 soccer players in Musi Rawas District. Pseudo-experiments are this kind of research. All athletes of PERSIMURA U-17 Kab. Musi Rawas will be used as a population for this study a total of 39 Musi Rawas players. The example in this study was taken using a relative testing method, namely a procedure based on the doctor's own consideration into an example of 16 people. The Illinois Agility Run test was used for the research instrument. The strategy of examining factual information uses the Liliefors regularity test and the t test at the importance level ɑ=0.05. This study found that the football agility of PERSIMURA U-17 Kab. Musi Rawas was significantly affected by shuttle-run training. Cross-running training has an impact on the readiness of PERSIMURA U-17 football in Musi Rawas District. Exercises known as zigzag running and shuttle running have very different effects on agility. The agility of PERSIMURA U-17 Football Players of Musi Rawas Regency is more influenced by zigzag running training than by shuttle run training.